2020
DOI: 10.1177/0271678x20941264
|View full text |Cite
|
Sign up to set email alerts
|

D-Glucose uptake and clearance in the tauopathy Alzheimer’s disease mouse brain detected by on-resonance variable delay multiple pulse MRI

Abstract: In this study, we applied on-resonance variable delay multiple pulse (onVDMP) MRI to study D-glucose uptake in a mouse model of Alzheimer’s disease (AD) tauopathy and demonstrated its feasibility in discriminating AD mice from wild-type mice. The D-glucose uptake in the cortex of AD mice (1.70 ± 1.33%) was significantly reduced compared to that of wild-type mice (5.42 ± 0.70%, p = 0.0051). Also, a slower D-glucose uptake rate was found in the cerebrospinal fluid (CSF) of AD mice (0.08 ± 0.01 min−1) compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 61 publications
(77 reference statements)
2
65
0
1
Order By: Relevance
“…Former publications of 2 H-labeled glucose metabolic flux at the brain mainly included animal experiments ( Kreis et al., 2020 ; Chen et al., 2021 ; Lu et al., 2017 ; Rich et al., 2020 ; de Graaf et al., 2021 ). Only a very limited number of experiments were conducted on the human brain ( De Feyter et al., 2018 ; de Graaf et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Former publications of 2 H-labeled glucose metabolic flux at the brain mainly included animal experiments ( Kreis et al., 2020 ; Chen et al., 2021 ; Lu et al., 2017 ; Rich et al., 2020 ; de Graaf et al., 2021 ). Only a very limited number of experiments were conducted on the human brain ( De Feyter et al., 2018 ; de Graaf et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The water natural abundance of 2 H is very low (> 0.015% before and 0.0115% after correction for tissue water fraction) ( Zhu and Chen, 2018 ; De Feyter and de Graaf, 2021 ), which makes it very suitable for the application as a tracer. Different potential applications of 2 H MRS were already investigated in animal models, including chemotherapy response ( Kreis et al., 2020 ), Alzheimer's disease ( Chen et al., 2021 ), adiposity ( Riis-Vestergaard et al., 2020 ), visibility of liver glycogen ( HM De Feyter et al., 2021 ) and monitoring of tumor cell death ( Hesse et al., 2021 ). Especially in cancer research, the application of deuterated glucose to investigate the glycolytic flux as well as the Warburg effect seems very promising, which was shown for animal models as well as human patients ( De Feyter et al., 2018 ; Lu et al., 2015 ; Lu et al., 2016 ; Kreis et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of AD would allow earlier treatment of people at risk, which will likely improve the performance of clinical trials. Many non-invasive biomarkers have been investigated for detecting AD, such as (i) the accumulation of neuritic plaques, which consist of an amyloid-beta (A β ) core ( Hardy and Selkoe, 2002 ; Selkoe and Kopan, 2003 ) and neurofibrillary tangles (NFT) that are composed of hyperphosphorylated tau ( Ballatore et al, 2007 ; Lee and Trojanowski, 1999 ; Rojas and Boxer, 2016 ) in brain detected by positron emission tomography (PET) imaging ( Saint-Aubert et al, 2017 ); (ii) levels of A β and tau in cerebrospinal fluid (CSF) ( Barthelemy et al, 2020 ; Paterson et al, 2019 ); (iii) reduced glucose metabolism measured by 2-deoxy-2-( 18 F) fluoro-D-glucose ( 18 FDG) PET ( Mosconi et al, 2009 ) or MRI ( Chen et al, 2021 ; Huang et al, 2020 ); (iv) brain atrophy revealed by structural imaging using MRI and CT ( Frisoni et al, 2010 ). Despite the great detection sensitivity of PET imaging, the high cost and the use of radioactive tracers hinder its wide clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The T1, T2, and apparent diffusion coefficient (ADC) are significantly different between CSF (T1=3.0 s, T2= 300 ms at 11.7T; ADC=3 µm 2 /ms) and ISF (T1=1.8 s, T2= 40 ms at 11.7T; ADC=0.7 µm 2 /ms). (36,38) In principle, T1, T2, or ADC can selectively label either CSF or ISF to monitor the ISF-CSF exchange process. However, in practice, it is a challenge to label CSF without attenuate ISF and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…However, examining CSF and ISF exchanging process still relied on MRI contrast agents such as the intra-cranial (19,(29)(30)(31)(32) or intrathecal injection (33)(34)(35) of gadolinium-based contrast agents and intravenous D-glucose infusion. (36,37) Contrast agent-based MRI methods are far from ideal for routine and repeated measurements on patients.…”
Section: Introductionmentioning
confidence: 99%